Holidays and atopic eczema. Issue 2 (February 1991) - Turner, M A; Devlin, J; David, T J
Abstract : Information was collected by telephone about 300 holidays taken over a three year period by 126 children with severe atopic eczema. During the holidays, improvement in eczema occurred more frequently (112/300, 37%) than deterioration (63/300, 21%). There was a significant correlation between improvement and a more southerly holiday location: improvement was common in holidays taken in the Mediterranean or further south (63/92, 69%), but holidays in northern Britain were more likely to be associated with deterioration (27/100, 27%) than improvement (13/100, 13%). Changes in eczema were correlated with changes in asthma in 231 holidays taken by children with both conditions, but improvement was not significantly associated with pet ownership. All patients returned to their preholiday state, usually within two weeks of return home. The causes of changes in eczema while on holiday have not been identified.